THE ROLE OF EDUCATIONAL TECHNOLOGIES IN TEACHING - Yuldashova Umida Bakhtiyar qizi (Research Parks Publishing LLC, 2021)
The article deals with the educational technologies in teaching process. Educational technology is as an essential element of training students. In other word, educational technology is the innovative form of teaching, methods and tools help to improving the condition in educational process. To create new pedagogical technology is very difficult. One of the important part of improving teaching is to practice and working hardly. Article analyses the developing of classroom technology to get result in education. Teacher skills and key issues of educational technology